Development and validation of a tropical diatom-based index for bioassessment of the Yang River, Northern Thailand - SUTTAYOT YIMPOOLSAP (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Yimpoolsap S. 2026. Development and validation of a tropical diatom-based index for bioassessment of the Yang River, Northern Thailand. Biodiversitas 27 (2): d270206. https://doi.org/10.13057/biodiv/d270206. Freshwater ecosystems in tropical Asia are increasingly threatened by nutrient enrichment, organic pollution, and land-use intensification. Diatoms are widely recognised as sensitive biological indicators, yet most available diatom indices were developed for temperate regions and may not adequately reflect ecological conditions in tropical rivers. This study aimed to develop a regionally calibrated, river-specific Diatom Index using the Yang River, Northern Thailand, as a model tropical system for water quality assessment. Water sampling and benthic diatom collection were conducted across seven stations from November 2016 to April 2017. Physico-chemical parameters were analysed according to American Public Health Association (APHA 2017), and diatom assemblages were identified to the lowest possible taxonomic level. Indicator Values (IV) and Weighted Averages (WA) were computed for 29 dominant taxa, and the final Diatom Index (DI) was validated against the conventional Water Quality Index (WQI). The study addresses a key methodological limitation in tropical bioassessment by developing an index based on observed ecological responses of tropical diatom assemblages, rather than relying on tolerance values derived from temperate regions. Reproducibility was evaluated using three independent chemistry replicate datasets (R1-R3), which showed high consistency in WA/IV estimation and DI computation (ρ = 0.860-0.907, p < 0.001), indicating that the index-building process was robust and repeatable. The DI showed a significant positive relationship with WQI (ρ = 0.549, r² = 0.3102, p < 0.001), indicating that diatom assemblages effectively captured nutrient and organic pollution gradients. Spatial variation in diatom communities aligned with upstream-midstream-downstream differences in pH, DO, BOD, and nutrient levels. While developed from a single river system, the index provides a regionally appropriate and ecologically meaningful framework for diatom-based water quality assessment in tropical rivers, subject to further validation across additional catchments. The index offers a cost-effective and regionally calibrated approach for routine monitoring and supports improved management of tropical freshwater ecosystems.